Optimalisasi Mixed Light dalam Fotografi Produk: Workshop untuk Teman Tuli Surakarta - Ayuningtias BP; Wahyu Sukma Nada; Kristina Novi Susanti (Institut Seni Indonesia Surakarta, 2025)
Product photography training is one of the relevant empowerment efforts to support the potential of the deaf community in the era of the creative economy. Deaf individuals have advantages in the visual field; however, limited access to practical training often becomes an obstacle to selfdevelopment. This activity aims to optimize the use of mixed light techniques, which combine natural light and artificial light, in product photography practices through an inclusive workshop. The method used was direct practice at the DPC Gerkatin Surakarta location with a visual approach and the use of sign language to ensure full accessibility for the participants. The workshop was held on May 24, 2025, with a total of 15 participants. The training materials included basic product photography, lighting principles, and hands-on practice using mixed light techniques. The results of this activity showed an increase in participants' understanding of lighting techniques and their ability to produce product photos suitable for promotional purposes. This workshop also improved participants' self-confidence and opened opportunities for skill development in the creative economy sector. The activity proved that an inclusive and practicebased photography approach can be an effective means of empowerment for the deaf community. Keywords: deaf community, product photography, mixed light